Our noisy world. - Navarra, John Gabriel (Doubleday, 1969)
Discusses the physics of sound, the human hearing mechanism, and the modern problem of noise pollution, explaining both the beneficial and harmful effects of noise and suggesting some solutions to the noise problem.